신생아중환자실에서의 가족중심돌봄 기반 가족중재연구에 대한 통합적 문헌고찰 - 정나리; Chung Nary; 김예슬; Kim Yeseul; 박은영; Park Eunyoung; 여리사; Yeo Lisa; 황지원; Hwang Jiwon (Perspectives in nursing science, 2019)
Purpose: The aim of this study is to analyze the characteristics of family interventions based on a philosophy of family-centered care conducted in neonatal intensive care units through an integrative literature review. Methods: We searched the PubMed, CINAHL, RISS, KISS, and DBpia databases; a total of 20 studies, published between January 2013 and May 2018, was selected according to our criteria. Results: Mothers accounted for a greater proportion of participants in family interventions than did fathers. Family interventions described in the studies were categorized into four educational and sixteen non-educational interventions. Among non-educational interventions, skin-to-skin-contact interventions, such as kangaroo care, accounted for the highest proportion. Only one paper employed a theoretical framework. Conclusion: More family interventions based on theoretical frameworks should be conducted as these frameworks serve as guidelines for nursing research. As the stress patterns experienced by parents in neonatal intensive care units showed gender differences, more programs tailored for fathers are needed. Moreover, further research should be conducted to evaluate feasibility as an outcome variable, and studies of family interventions based on a philosophy of family-centered care should be performed more actively in the neonatal intensive care units in Korea.